ТРАНСФОРМАЦІЯ ІНСТИТУЦІЙНОЇ АРХІТЕКТУРИ БЮДЖЕТНОЇ СИСТЕМИ УКРАЇНИ (Світ фінансів, 2017)
Чуркіна І. Є. Трансформація інституційної архітектури бюджетної системи України. Розглянуто особливості трансформації інституційної архітектури бюджетної системи України, визначено необхідність переосмислення основ традиційної економічної теорії стосовно природи фінансово-економічних трансформацій. Відображено авторську позицію щодо основних проблем інституційного характеру, розкрито протиріччя еволюції інститутів бюджетної системи, представлено перелік інститутів розвитку бюджетної системи України у подальшій перспективі, проаналізовано ефективність їх дії. Чуркина И. Е. Трансформация институциональной архитектуры бюджетной системы Украины. Рассмотрены особенности трансформации институциональной архитектуры бюджетной системы Украины, определена необходимость переосмысления основ традиционной экономической теории относительно природы финансово-экономических трансформаций. Отображена авторская позиция в отношении основных проблем институционального характера, раскрыты противоречия эволюции институтов бюджетной системы, представлен перечень институтов развития бюджетной системы Украины в дальнейшей перспективе, проанализирована эффективность их действия. Churkina I. Transformation of institutional architecture of Ukraine’s budget system. Introduction. Rationally constructed and balanced budget system provides effective and efficient social and economic policy of the country. It provides substantial redistribution of financial resources and their areas of focus and ways of using largely depends on the economic development of the country and the real well-being of citizens. In the absence of an effective budget system the economic policy of the country will not be effective. An important aspect of the problem of architecture current budget system is its vertical dimension.Purpose. The aim of the article is the research of the characteristics of the transformation of the institutional architecture of the budget system of Ukraine and the determination of the contradictions of institutions` evolution.Results. The features of the transformation of the institutional architecture of Ukraine`s budget system are reviewed; the necessity of rethinking of the foundations of traditional economic theory about the nature of financial and economic transformations is defined. The author’s position according to the institutional issues is reflected, the contradictions of institutes` evolution of budget system is revealed, a list of the institutions of the development of budget system in Ukraine in the long run is presented, and the effectiveness of their actions is analyzed.Conclusion. In the evolution of the institutions of budget system the apparent contradiction is observed. On the one hand, it takes place in line with the general trend of strengthening the central government and strengthening redistribution function of public finances. On the other hand, the country with the aim of improving the use of centralized fiancial resources is trying to create an analogue of competitive market of their distribution. But in Ukraine these attempts stumble to “trap” of public sector of the economy. Building of an efficient and competitive economy requires the systemic reform of public finance sector, its problems and contradictions today are key risks for the quick recovery of economy in Ukraine. The effectiveness of economic policies depends not only by how much money was mobilized to the budget, but also by how effectively they are re-allocated and spent.